Determining the Relationship between Squat Jump Performance and Knee Angle in Female University Students - Felice Di Domenico; Giovanni Esposito; Sara Aliberti; Francesca D’Elia; Tiziana D’Isanto (Journal of Functional Morphology and Kinesiology, 2024)
The Squat Jump (SJ) test is widely recognized as a reliable test for assessing lower-limb explosive strength. However, uncertainty persists in the literature regarding the optimal starting positions for maximizing vertical jump performance. This uncertainty is exacerbated by a disproportionate focus on athletes in existing studies, with insufficient consideration being given to non-athletic women. To address this gap, this study investigated the influence of leg starting angle on explosive jump height in a homogeneous sample of non-athletic women. Thirty-two female students enrolled in a Sports Science master’s degree program at the University of Salerno participated in the study. Descriptive statistics were employed to summarize data on various variables, and Pearson’s correlations were calculated to assess the relationship between knee angle in the starting position and achieved jump height. The study revealed that different starting positions had a noteworthy impact on jump height among the participants. A strong negative correlation (−0.701) was identified between Squat Jump elevation and the knee angle in the starting position. Notably, 62.5% of the subjects opted for a starting knee position of approximately 70 degrees, with all of them consistently achieving a jump height associated with this specific angle. These findings provide valuable insights into the relationship between leg starting angle and explosive jump height in non-athletic women. The observed correlation underscores the significance of the starting position in Squat Jump performance. The prevalence of a specific knee angle choice among participants suggests potential implications for training and performance optimization in this sample.